Rock endpoints and barriers estimation of slope failure in Pinousuk Gravel slopes using Rocfall simulation - H F W S Erfen; Baba Musta (IOP Publishing Ltd, 2022)
The research is conducted to simulate the possibility of rock fall occurrences in the study area. The study area is located at highland area in Mesilou, Kundasang, Sabah which consists of Late Pleistocene age of tilloid deposits namely Pinousuk Gravel. Four slopes of Pinousuk Gravel were selected to estimate the distance of rock endpoints and the locations of barriers to minimize the damage when slope failure occurs by using ‘Rocfall’ simulation software. The software is commonly used for risk assessment of potential rock slope failure. The result of analysis shows the rock endpoints distance ranges from the 3.1 meters to 4.9 meters from the foot of the slope with bounce height from 0.6 meters to 2.2 meters during downfall. Based on total amount of kinetic energy on each slope, the location of the proposed barrier is within 1 meter to 4 meters from the slope foot. As a conclusion, the rock endpoints depend on slope height and angle, while the proposed location for barrier is based on its ability to withstand the kinetic energy released during slope failure.